Polemik Antara Original Event dan Original Purpose dalam Liturgi: Spiritualitas Liturgi Ekaristi dalam Perspektif Sejarah Liturgi dan Kitab Suci - Robert Pius Manik (Studia Philosophica et Theologica, 2021)
Abstract This article discusses the basic character of the Roman liturgy and examines what the original Roman liturgical rite is that can serve as a standard for the Roman liturgical rites. Discussion about the authenticity of the Roman rites often lead to endless debate and create difficulties in practical matters when some of the rites are applied to liturgical celebrations. The analysis of the authenticity of the Roman rite in this paper will be based on the views of Edmund Bishop, an English liturgical historian. Besides using a historical approach, this article will also use a biblical study approach in exploring the basic characteristics of the Catholic liturgy, especially the Eucharist, so that a celebration of the Eucharistic liturgy can be said to be good. The views of several exegetes such as Brevard S. Childs (Old Testament) and Joachim Jeremias and Xavier Leon-Dufour (New Testament) will be used to analyze the biblical texts, especially regarding the story of the celebration of the Jewish Passover, Exodus and the story of the Last Supper in connection with the Eucharist. And, of course the opinions of contemporary liturgical historians such as Paul F. Bradshaw and John Maxwell are also very important here in order to discover the relevance of this study today.